Maternal uniparental disomy of the chromosome 14: need for growth hormone provocative tests also when a deficiency is not suspected. Issue 5 (10th May 2019) - Tortora, Anna; La Sala, Domenico; Lonardo, Fortunato; Vitale, Mario
Abstract : Uniparental disomy (UPD) is a congenital disease characterised by the presence of two homologous chromosomes inherited from one parent in a diploid offspring. Maternal UPD of the chromosome 14 (UPD(14)mat, Temple syndrome) is a rare disorder with heterogeneous clinical presentation. Here, we report a case of UPD(14)mat with a small supernumerary marker chromosome in a 6-year-old baby girl, presenting endocrinological disorders and incomplete clinical presentation. She came to our attention because of precocious beginning of pubarche and normal stature. Most of Temple syndrome signs were lacking. Provocative tests diagnosed incomplete growth hormone (GH) response and confirmed precocious puberty. One year treatment with recombinant human GH and gonadotropin-releasing hormone (GnRH) agonists proved successful, increasing height and arresting puberty. We recommend provocative tests for GH in UPD(14)mat as a GH deficiency can be hidden by a concurrent precocious puberty. Concomitant human GH and GnRH analogue treatment can be pursued.